(3eLehYI aj GdgfOSIs - (3GhWhdhbSs
(3ChdgG (B:s
(3hgh ebGdJGf hSJI hKdGKhf TcdkG GdebGdI GdChdi dHYV WdhYGJ GdchGcH gh Cf jWdY GdchcH YfO WdhY GdTeS hGdZQhH s
(3BNQgG (B:s
(3hPdc eG CQOfGg gPG BNQ GdebGdI GdKGfjI hJe GdcJGH HYhf Gdgd hMSf Jhajbg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1435s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs